Participatory management in recovery degraded area by agriculture - Checoli, Carlos Henrique Bonsi; Shiraiwa, Shozo; da Silva, Marcelo Correa; Silva, Normandes Matos da (Sociedade & Natureza, 2016)
Researchers at Federal University of Mato Grosso (UFMT) subsidized a strategy for participatory management, in order to plan and implement a degraded area recovery plan (DARP) in the permanent preservation area at the basin of the São Lourenço river, in Campo Verde, municipality prominent in Mato Grosso and Brazil agribusiness. Research was carried out using group dynamics that are often applied in quality management standards ISO 9001. There was little interaction between local actors in terms of implementation of environmental recovery actions. The economic cost of deployment and maintenance of DARP is a bottle neck. The lack of perspectives to consider DARP as a productive area was also limiting point in farmers perspectives. The research that UFMT undertook strengthened efforts in order to reduce degradation that currently occupies around 33% of the State of Mato Grosso.